Implementation of Jembrana Regency Regional Regulation Number 1 Of 2019 Concerning Child-Friendly DistrictsiIn Jembrana District Jembrana Regency in 2020 - Ni Putu Satya Wirantari; Agus Joko Purwanto; Ade Reza Hariyadi (International Journal Labs, 2022)
Background: The implementation of Regulation of The Regency of Jembrana Number 1 of 2019 is an effort by local governments to create Child-Friendly Regency (KLA) and Child-Friendly Districts (Kelana). Objective: This study aims to analyze the implementation of Child-Friendly Regency/City (KLA) development policies, especially Child-Friendly Districts (Kelana), to identify factors that support the implementation of Child-Friendly Regency/City development policies (KLA), especially Child-Friendly District (Kelana) and to identify factors that become obstacles in the implementation of Child-Friendly Regency/City development policies in Jembrana District Jembrana Regency. Method: This type of research uses descriptive research with a qualitative approach. Result: In this study, the researcher adopted the post-positivism paradigm. According to this paradigm, the relationship between the observer or researcher and the object or reality under study cannot be separated. The post-positives paradigm assumes that reality does exist and is in accordance with reality and natural laws, but it is impossible for researchers to see that reality correctly. Conclusion: Based on the indicators of child-worthy districts for institutional strengthening, there are available Regional Regulations/Policies on Child-Worthy Districts/Cities in the process of drafting regional regulations/policies and implementing regulations/policies, programs, and activities to realize KLA Regional Regulation Number 1 of 2019 concerning Child Worthy Districts in Jembrana Regency already paying attention to the views of children.